CHARACTERISTICS OF FAMILIES AND FAMILIES THAT HAVE STUNTING IN MORE VILLAGE GIANYAR DISTRICT - I Gusti Agung Mas Candyas Pradnyaditha; Hertog Nursanyoto; A.A. Raka Kayanaya (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
The results of PSG 2017, in Indonesia it was found that 29,6% of children under five had stunting with 9,8% of children under five with very short nutritional status and 19,8% of children under five had a short nutritional status. The percentage of stunting infants in Over Village Gianyar Regency (31,1%) is still higher than the prevalence of stunting toddlers in Bali Province (19,1%). Toddlers who have increased stunting are more likely to move 36-47 months (57,9%) and male sex (68,4%) but most have Normal birth weight (90,5%). The characteristics of the family of children under five who are stunted are seen from father's education (36,8%) and the education of under-five mothers (47,4%) more educated and seen from the work of all fathers and mothers working with economic status more prosperous families namely (57,9%). There are differences of opinion about stunting in toddlers in the village of Over Regency Gianyar based on the age of the toddler and sex but not found based on the birth weight. There were differences in the incidence of stunting in infants based on family characteristics. Kepada Masyarakat Especially for pregnant women and families who have babies or toddlers who are approved to implement a program related to 1000 HPK by routinely visiting posyandu.